Factors Affecting Production And Income As Well As The Level Of Efficiency Of Arabika Coffee Production (Coffea Arabica) In Huta Bagasan Village, North Dempo District Humbang Hasundutan Regency - Susila, Annas Dinurohman; ., yunita (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2024)
The objectives of this research are: (1) to analyze the factors that influence Arabica Coffee production in Huta Bagasan Village, Dolok Sanggul District, and Humbang Hasundutan Regency using multiple linear regression analysis approaches and socio-economic survey data, (2) Using an income level analysis approach and survey data, examine the level of income of Arabica coffee farmers in Huta Bagasan Village, Dolok Sanggul District, and Humbang Hasundutan Regency (3) To analyze the efficiency level of Arabica Coffe farming production in Huta Bagasan Village, Dolok Sanggul District, and the Regency of Humbang Hasundutan. This research was conducted in Huta Bagasan Village, Dolok Sanggul District, and Humbang Hasundutan Regency with a total of 34 coffee farmers who were selected using the sample random sampling method, which is processed with SPSS and determines the value of the marginal product. This study uses primary and secondary data. The results of this study indicate that the production factors that have a significant effect on production yields are land area, and urea fertilizer. While NPK fertilizer, labor and herbisida do not have a significant effect. The average income of coffee farmers in Huta Bagasan Village is Rp 36.035.917 per hectare per year. For the efficiency of production factors that must be reduced, their use is land area and pestisida, because it is not efficient. while the production factors that are not efficient and need to be used more are labor, urea fertilizer, and NPK fertilizer. keyword: arabika coffee farmer, efficiency, production factor, production